STUDY ON RUMPUT MUTIARA (Hedyotis Corimbosa) HERBS AS MEDICINE - Soemardji, Andreanus A.; Anisa, Ita N.; Damayanti, Nareswari Alka (Maranatha Christian University, 2015)
âRumput Mutiaraâ or Pearl grass (Hedyotis corymbosa) is one of medicinal plants used empirically by the Indonesian people to cure disease to maintain health. Many people have used pearl grass for a long time. This plant contains hentriacontane, stigmasterol, ursolic acid, oleanolicacid, Î²-sitosterol, sitisterol-D-glucoside, p-coumaric acid, flavonoid-glycosides, âbaihua she she cao suâ (possibility coumarin analog), iridoid glycosides, alizarin, korogenin, and bonding antragalol.Â Herbaceous plant is used and effetive as a relieve fever (antipyretic), anti-inflammatory, antibacterial, laxative urine(diuretic), removes heat and toxins (detoksikan), blood circulation, anti-cancer, the treatment of peptic ulcers, dysentery, exhausted maternity, and indigestion. This review article is a compilation of Hedyotis corymbosa herb as traditional medicinal plant and pharmacological researches of this herb that can be use as ethnopharmacological and pharmacological information of this medicinal herb.Â Keywords: Â Pearl grass, Hedyotis corymbosa, medicinal plants, ethnopharmacology, pharmacology.